CI-UNA: Empowering the Professional Development of the University Graduate - Olivares Garita, Cinthya (2020)
Since 1973, Universidad Nacional (UNA), one of the most prestigious public universities in Costa Rica, “has fostered a holistic formation of the students and permanent education that must prepare them to act as responsible citizens and contribute to developing a more just and caring society” (Universidad Nacional, 2005, p. 5). One element of substantive action is the social extension and knowledge transfer. From 2010 to present, the Pérez Zeledón Campus implemented a project called CI-UNA (Centro de Idiomas, Universidad Nacional); it has a dual function. First, to develop competencies in the local citizens through teaching conversational English courses; and second, to offer job opportunities to graduate students from the English Teaching Major of this campus. This exploratory study aims to analyze the role of the project CI-UNA as an important mechanism for English Teaching alumni to enter the job market and establish the influence of this project in the instructors’ professional growth. The major results evidence the significant role of CI-UNA as a generating project of a qualified group of teachers in areas like heterogeneous group management, development of appropriate activities for the students, and organization and planning of communicative classes. Furthermore, this project is recognized as a great job opportunity, personal growth, and professional development.